PENGARUH PELATIHAN SUMBER DAYA MANUSIA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT PLN (PERSERO) WILAYAH SULUTTENGGO AREA MANADO (JURNAL ADMINISTRASI BISNIS, 2016)
Abstract.This research was conducted to find out how big the influenceof Training human resources (HR) against work productivity ofemployees At PT. PLN (Persero) Area of Manado.From the results of theresearch note that the training of human resources (HR) has a verystrong Influence and is an important factor to increased Employee Productivity,PT. PLN (Persero) Area of Manado.Where human resources Training have aninfluence of 86.8% Employee to productivity and 13.2% set by factors that are notin this meticulous research such as leadership, compensation, work environment,placement, and other variables. It can be concluded that the training of HUMANRESOURCES towards significantly influential work productivity of employees atPT. PLN (Persero) Area ofManado. This is because the Training of HUMANRESOURCES is a strong factor to encourage morale or employee passion forplacing certain activities in maximing the Productivity of work. Recommendationsfor the Management of HUMAN RESOURCES is maintained as well as improvingthe quality of training because training variables influence isdominant in affecting employee productivity, including through improvements inmaterials, methods and training tutuors so that employee productivity will increase.Keyword: Training, Human Resources, Employee Productivity